Stability analysis of higher-order delta-sigma modulators for sinusoidal inputs - Lota, Jaswinder; Al-Janabi, Mohammed; Kale, Izzet (Institute of Electrical and Electronics Engineers Inc., 2007)
The aim of this paper is to determine the stability of higherrorder ?-? modulators for sinusoidal inputs. The nonlinear gains for the single bit quantizer for a. dual sinusoidal input have been derived and the maximum stable, input limits for a fifth-order Chibyskev Type II based ?-? modulators are established. These results are useful for optimising the design of higherr order ?-? modulators. © 2007 IEEE.
2007 IEEE Instrumentation and Measurement Technology, IMTC 2007 - Synergy of Science and Technology in Instrumentation and Measurement --
Keywords: Gain measurement; Input output programs; Linear stability analysis; Optimization; Input limits; Nonlinear gains; Single bit quantizers; Sinusoidal inputs; Delta sigma modulation